Afforestation of Beel Areas in Malda Forest Division - Biswas, G. S. (Indian Forester, 1960)
The Maida forest division with its beel areas ( swamps) is confronted with serious problems of afforestation with useful tree species. The great fluctuation of water level on the land and various other adverse climatic factors create serious difficulties. The development of the plantation techniques has been discussed.